Relation between Access Blood Flow and Mortality in Chronic Hemodialysis Patients - Al-Ghonaim, Mohammed (American Society of Nephrology, 2008)
Background: Access blood flow (Qa) measurement is a potentially important determinant of systemic hemodynamics in hemodialysis patients. High Qa may contribute to left ventricular dilation and high output heart failure. On the other hand, low Qa might lead to underdialysis, which is associated with adverse outcomes. Methods: In this retrospective study of incident chronic hemodialysis patients treated in three Canadian cities (Edmonton, Calgary, and Halifax), the hypothesis that extremes of Qa(low or high) would be associated with increased mortality was tested. The distribution of Qa was not Gaussian, and therefore Qa was log-transformed in analyses that treated it as a continuous variable. Qa was classified into categories defined by cutpoints of 500, 1000, 1500, and 2000 ml/min. Univariate and multivariate Cox proportional hazard models were performed to examine the relation between Qa and all-cause mortality. Patients were followed from the date of Qa measurement until death; follow-up was discontinued at loss to follow-up, kidney transplantation, or end of study. Results: Of 820 participants, those with lower levels of Qa tended to be older and to have more comorbidities. During the median follow-up period of 28 mo, 206 (25.1%) participants died and 101 (12.3%) patients received a kidney transplant. When only baseline measures of Qa were considered, there was significant association between Qa and mortality [hazard ratio (HR) per unit increase in logQa 0.81, 95% confidence interval (CI) 0.67, 0.97; adjusted HR per unit increase in logQa 0.90, 95% CI 0.72, 1.11]. The adjusted risk of mortality was similar between the different categories of baseline Qa before and after adjustment for demographic characteristics, comorbidity, and access type. In analyses that included all Qa measurements per patient as a time-varying covariate, the adjusted association between Qa and death remained nonsignificant, with no evidence of increased mortality at higher Qa (HR per unit increase in logQa 0.82, 95% CI 0.67, 1.01, P = 0.066). Conclusion: The findings of this study do not suggest an increased risk of death at higher levels of Qa, Further studies would be needed to confirm an increased risk of death at lower Qa.